1999
DOI: 10.1007/pl00013182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Carbohydrate Antigen 195 and Carcinoembryonic Antigen for the Diagnosis of Pancreatic Carcinoma

Abstract: The expression CA195 in serum, defined by monoclonal antibody CC3C195 (IgM), was studied in 67 patients with pancreatic cancer and in 138 patients with biliary or pancreatic benign disease. The results were compared with carcinoembryonic antigen (CEA) expression. The overall sensitivity of the CA195 assay (> 12 U/ml) was higher than that for CEA (89.5% vs. 53.7%) (p < 0.001). Sensitivity was increased to 92.5% with the simultaneous use of the two antigens, but the difference was statistically significant only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The main reason for the lack of large studies on early-stage pancreatic cancer has been the difficulty in obtaining the samples. Typical biomarker studies in pancreatic cancer include a small minority of stage I/II patients, such as a study in which 10 of the 67 pancreatic cancer patients had stage I/II disease [ 31 ]. Many studies do not specify the stage of the patients but likely involve mostly late stage patients because samples from late-stage patients are more readily available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for the lack of large studies on early-stage pancreatic cancer has been the difficulty in obtaining the samples. Typical biomarker studies in pancreatic cancer include a small minority of stage I/II patients, such as a study in which 10 of the 67 pancreatic cancer patients had stage I/II disease [ 31 ]. Many studies do not specify the stage of the patients but likely involve mostly late stage patients because samples from late-stage patients are more readily available.…”
Section: Discussionmentioning
confidence: 99%
“…The variance between the results of our study and those of some previous studies may be due to differences in the selection of the chronic pancreatitis patients, for example due to greater care in this study to select confirmed chronic pancreatitis patients in a quiescent state. In any case, the observations of higher CA 19–9 levels in cancer relative to chronic pancreatitis have led some to suggest the use of higher thresholds (>100 U/mL) for the differential diagnosis of pancreatic cancer from chronic pancreatitis [ 31 , 32 , 34 , 35 ]. Our study confirmed that elevations can be confirmatory for stage I-II pancreatic cancer with a sensitivity of ~70% at thresholds that give near perfect specificity.…”
Section: Discussionmentioning
confidence: 99%